Oxygen injury in neonates: which is worse? hyperoxia, hypoxia, or alternating hyperoxia/hypoxia - Mohamed, Tarek (J Lung Pulm Respir Res, 2020)
Premature birth results in an increased risk of respiratory distress and often requires oxygen therapy. While the supplemental oxygen has been implicated as a cause of bronchopulmonary dysplasia (BPD), in clinical practice this supplementation usually only occurs after the patient’s oxygen saturation levels have dropped. The effect of hyperoxia on neonates has been extensively studied. However, there is an unanswered fundamental question: which has the most impact-hyperoxia, hypoxia or fluctuating oxygen levels? In this review, we will summarize the reported effect of hypoxia, hyperoxia or a fluctuation of oxygen levels (hypoxia/hyperoxia cycling) in preterm neonates, with special emphasis on the lungs.